(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Studies have been done in seven hatchenis in in Mahawil district/Babil from the period 15/3 to 15/5 to identify the body and reproductive characteristics between common carp brood stock which was imported in 2009 containing this shiny line of scales that exists dorsal fin of carp and which is without shiny line of scales was imported in 1982. Body characteristic results showed significant difference P ‹ 0.05 between two brood stock according to body depth/standard length feature, so they reached an average of this feature in common carp shiny line of scales 0.003 ± 0.389 higher than those containing no shiny line reached 0.002 ± 0.369, whereas no significant differences was shown between two brood stock for fish weight and head length/ standard length. Reproductive characteristic study showed significant difference P ‹ 0.05 for shiny line brood stock for each total eggs weight(gm) , eggs number /gm eggs , eggs weight/kg fish and fertilization percentage characteristic , which reached an average of 26.62 ± 520.28, 4.46 ± 764.60, 94.76 ± 159.2, 0.33 ± 82.91 respectively, higher than of those without shiny line brood stock which reached average of 21.32 ± 461.42, 4.44 ± 711.15, 4.42 ± 147.73 respectively, whereas significant difference was shown in egg diameter characteristic for containing no shiny line brood stock which reached 0.01 ± 1.411 where brood stock of shiny line reached average of 0.01 ± 1.38 and no significant differences were showed between two brood stock in eggs number/ kg fish. That an increase of crossbreeding between different lines for common carp of brood stock do in improve somatic and reproductive characteristics of inbreeding and prevents deteriorating.